DESIGN OF KITCHEN SECURITY SYSTEM BASED ON ATMEGA32 MICROCONTROLLER - Aulia Khusnul Arif Z.A; Nazaruddin Nasution; Abdul Halim Daulay (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2019)
The kitchen is one of the places most concerned by every community because the biggest fire potential in the house lies in the kitchen, the source of fire that often causes fires in the kitchen is a stove and gas. Therefore we need a design of a kitchen security system based on the ATmega32 microcontroller using flame sensors, MQ-2 and MQ-6. This study aims to produce a performance tool that will detect any movement of fire, gas, and smoke using an Early Warning System. The warning in the form of an alarm sounds, the fan turns, and the door opens automatically. Sensor detection is designed with 4 conditions namely Normal, Caution, Alert and Danger. The results of testing using the Flame sensor found a wave range from 22 nm to 1022 nm from normal to hazardous conditions, the MQ-2 found the results of testing from the ADC (Analog Digital Converter) with concentrations from 0 ppm to 130 ppm from normal to hazardous conditions, and the MQ-6 test results were obtained from the ADC (Analog Digital Converter) with concentrations from 0 ppm to 520 ppm from normal to dangerous conditions. Keywords : Kitchen, ATmega32, Flame sensor, MQ-2, and MQ-6.